Evaluation and Management of the Child and Adult With Fontan Circulation: A Scientific Statement From the American Heart Association. Issue 6 (6th August 2019) - Rychik, Jack; Atz, Andrew M.; Celermajer, David S.; Deal, Barbara J.; Gatzoulis, Michael A.; Gewillig, Marc H.; Hsia, Tain-Yen; Hsu, Daphne T.; Kovacs, Adrienne H.; McCrindle, Brian W.; Newburger, Jane W.; Pike, Nancy A.; et al.
Abstract : It has been 50 years since Francis Fontan pioneered the operation that today bears his name. Initially designed for patients with tricuspid atresia, this procedure is now offered for a vast array of congenital cardiac lesions when a circulation with 2 ventricles cannot be achieved. As a result of technical advances and improvements in patient selection and perioperative management, survival has steadily increased, and it is estimated that patients operated on today may hope for a 30-year survival of >80%. Up to 70 000 patients may be alive worldwide today with Fontan circulation, and this population is expected to double in the next 20 years. In the absence of a subpulmonary ventricle, Fontan circulation is characterized by chronically elevated systemic venous pressures and decreased cardiac output. The addition of this acquired abnormal circulation to innate abnormalities associated with single-ventricle congenital heart disease exposes these patients to a variety of complications. Circulatory failure, ventricular dysfunction, atrioventricular valve regurgitation, arrhythmia, protein-losing enteropathy, and plastic bronchitis are potential complications of the Fontan circulation. Abnormalities in body composition, bone structure, and growth have been detected. Liver fibrosis and renal dysfunction are common and may progress over time. Cognitive, neuropsychological, and behavioral deficits are highly prevalent. As a testimony to the success of the current strategy of care, the proportion of adults with Fontan circulation is increasing. Healthcare providers are ill-prepared to tackle these challenges, as well as specific needs such as contraception and pregnancy in female patients. The role of therapies such as cardiovascular drugs to prevent and treat complications, heart transplantation, and mechanical circulatory support remains undetermined. There is a clear need for consensus on how best to follow up patients with Fontan circulation and to treat their complications. This American Heart Association statement summarizes the current state of knowledge on the Fontan circulation and its consequences. A proposed surveillance testing toolkit provides recommendations for a range of acceptable approaches to follow-up care for the patient with Fontan circulation. Gaps in knowledge and areas for future focus of investigation are highlighted, with the objective of laying the groundwork for creating a normal quality and duration of life for these unique individuals.